An Effective Approach for the Development of Reliable YBCO Bulk Cryomagnets with High Trapped Field Performances. (24th March 2014) - Kenfaui, Driss; Sibeud, Pierre‐Frédéric; Louradour, Eric; Chaud, Xavier; Noudem, Jacques G.
<x xml:space="preserve">Abstract</x> Widespread use of YBa2Cu3O7‐δ (Y123) bulk superconductors as source of strong magnetic fields requires development of high‐performance materials sufficiently reliable with improved thermal transfer ability. An effective approach based primarily on the growth of bulk Y123 single domains comprising a holes‐network to diminish the oxygen diffusion paths is reported here, as well as their progressive annealing at high temperature under oxygen pressure to reduce undue stresses and processing time. Finely, it aims to stimulate the thermal exchange inside the superconductor and compensate for induced magnetic stresses during the field‐trapping process. The approach brings considerable time and energy savings, and turns out to knock down barriers having stymied hitherto the use of Y123 bulk superconductors for engineering applications. Indeed, it enables the achievement of a pore‐free and crack‐free microstructure yielding marked fracture toughness and promoting large size persistent current loops, thereby boosting the trapped field performances. The fostering of the internal thermal exchange leads the maximum trapped field Bmax to shift to higher temperatures by up to 14 K. A value Bmax of 6.34 T is attained at 17 K on ≈16 mm‐diameter reinforced pellet (disk area s = 1.99 cm2), resulting in an outstanding field density Bmax/s=3.19 Tcm−2.